Melioidosis in Gujarat: a neglected tropical disease. (October 2020) - Savaj, Pratik; Shaw, Tushar; Munim, Frenil C; Mukhopadhyay, Chiranjay
We report what we believe is the first case in Gujarat of melioidosis in a 67-year-old man. Awareness of this disease is limited, especially in areas supposed not to be endemic.